Upper Limb Congenital Anomalies in Nigeria - David Odoyoh Odatuwa-Omagbemi (The Annals of African Surgery, 2020)
Background: About 1–2% of neonates have congenital anomalies; of these, 10% affect the upper limbs. Congenital anomalies are structural or metabolic defects present at birth. Objective: To review cases seen over a four-year period in a tertiary specialist hospital in Lagos and share our experience. Methodology: Case notes and theatre records of patients with congenital upper limb anomalies were retrieved and relevant data extracted. Data were analyzed with SPSS version 20. Results: 46 patients with 53 diagnoses of upper extremity congenital anomalies: 28 were males and 18 females between 5 weeks and 14 years. 17 patients (37%) presented within the first 12 months of life. Average ages of mothers and fathers were 34.1 and 37 years respectively. 26% of mothers had febrile illnesses and 28.3% used herbal products during the index pregnancies. Swanson’s group 2 was the commonest (58.4). Syndactyly was the commonest descriptive individual diagnosis (49%). Treatments were individualized according to specific diagnosis. Conclusions: Congenital anomalies of the upper extremities present as various diagnostic entities. Syndactyly was the most frequently encountered here